Religious Belief, Human Rights, and Social Democracy: Catholic Reflections on Abortion in Iceland - Giorgio Baruchello (The University of Akureyri, 2018)
Terms such as “pro-life” and “pro-choice” evoke animated responses in the Anglophone world and can even win, or lose, major elections to political parties, candidates and movements. In the Nordic countries, however, the same terms and related responses are generally perceived as academic, at best, or as American, at worst. The issue of abortion seems to have been settled long ago in the Nordic context, both legally and, above all, socially. Does it mean that it has also been settled ethically? I argue that this is far from being the case and present an Iceland-based approach to the issue that, while leaving women’s rights and freedoms untouched, can accommodate to an extent the defence of Scandinavian-style social democracy as well as the traditional Catholic defence of human life.